Molecular interactions, proton exchange, and photoinduced processes prompted by an inclusion process and a [2]pseudorotaxane formation - Mandal, Amal Kumar; Suresh, Moorthy; Kesharwani, Manoj K.; Gangopadhyay, Monalisa; Agrawal, Manoj; Boricha, Vinod P.; Ganguly, Bishwajit; Das, Amitava (Journal of Organic Chemistry, 2013)
Appropriate design of the host and guest components allows formation of a novel [2]pseudorotaxane complex with an interrupted photoinduced electron transfer (PET)-coupled fluorescence resonance energy transfer (FRET) response. This is the first example of an inclusion complex with NO6-based azacrown ether as the host unit (H). Different guest molecules (G1, G2, G3, and G4) with varying stopper size are used for the studies. Unlike G1, G2, and G3, G4 with a relatively bulkier stopper fails to form a [2]pseudorotaxane complex. Isothermal titration microcaloiimetry measurements reveal a systematic increase in the association constant for H.G1, H.G2, and H.G3 with a change in the stopper size. Thermodynamic data suggest that the formation of H.G1/H.G2/H.G3 is exclusively driven by a large positive entropic gain (T Delta S = 19.69/26.80/21.81 kJ.mol(-1)), while the enthalpy change is slightly negative for H.G1/H.G3 (-2.61/-1.97 kJ.mol(-1)) and slightly positive for H.G2 (Delta H = 5.98 kJ.mol(-1)). For these three inclusion complexes, an interrupted PET-coupled FRET response is observed with varying efficiency, which is attributed to the subtle differences in acidity of the NH2+ unit of the guest molecules and thus the proton exchange ability between the host and respective guest. This is substantiated by the results of the computational studies.